Research on the Protection and Utilisation Design Strategy of Hangzhou Traditional Villages on “Three Rivers and Two Banks” from the Perspective of Clusters - Wang Meiqi; Sun Yidong; Wu Zhe (SHS Web of Conferences, 2023)
At the beginning of 2023, Hangzhou launched the "Poetry Road Culture - Three Rivers and Two Banks" Water Golden Tourism Line Project, aimed at revitalizing the countryside in the western part of Hangzhou and creating a model area of common wealth. This article integrates natural and cultural resources on "Three Rivers and Two Banks" in Hangzhou, using kernel density analysis, proximity analysis, and weighted spatial superposition analysis of ArcGIS 10.8 software to classify the traditional villages on "Three Rivers and Two Banks" in Hangzhou into high-resource characteristic villages, intermediate resource characteristic villages, and general resource characteristic villages based on the distribution of resource characteristics. Finally, the traditional villages are examined within a systematic geographical framework to explore the establishment of traditional village cluster protection and development modes and methods. Strategies such as historical excavation, cluster construction, culture and tourism integration are proposed to achieve the goal of coordinating the rational allocation of regional resources, facilitating facility sharing, enhancing the endogenous dynamics of traditional villages, and forming distinctive village brand and cultural groups. This research aims to provide valuable insights for the protection of traditional village clusters.